2017
DOI: 10.1002/aenm.201602366
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering in Multinary Earth‐Abundant Chalcogenide Photovoltaic Materials

Abstract: IntroductionChalcogenide photovoltaic (PV) materials such as CdTe [1,2] and Cu(In,Ga)Se 2 (CIGSe) [3][4][5] have enabled remarkable progress in thin-film PV device performance, with each technology exceeding the 20% power conversion efficiency (PCE) barrier. However, two major concerns remain regarding these technologies-i.e., the negative environmental impacts of Cd Application of zinc-blende-related chalcogenide absorbers such as CdTe and Cu(In,Ga)Se 2 (CIGSe) has enabled remarkable advancement in laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
235
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(243 citation statements)
references
References 222 publications
(448 reference statements)
5
235
0
3
Order By: Relevance
“…17 Theoretical calculation demonstrated that the radius of Ag + (1.14Å) is substantially larger than that of Cu + (0.74Å) or Zn 2+ (0.74Å). 15 And the formation energy of Ag Zn defect (at 0.2 eV above the valence band edge) is much larger than that of the Cu Zn defect (0.12 eV). 16 There are several experimental studies reported the positive effects of the substitution of Cu by Ag on rigid glass substrates.…”
Section: -16mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Theoretical calculation demonstrated that the radius of Ag + (1.14Å) is substantially larger than that of Cu + (0.74Å) or Zn 2+ (0.74Å). 15 And the formation energy of Ag Zn defect (at 0.2 eV above the valence band edge) is much larger than that of the Cu Zn defect (0.12 eV). 16 There are several experimental studies reported the positive effects of the substitution of Cu by Ag on rigid glass substrates.…”
Section: -16mentioning
confidence: 99%
“…These results are in accordance with previous reports. 15,19,20 The XRD patterns of some binary and ternary selenide, such as ZnSe, and Cu 2 SnSe 3 , are similar to that of CZTSSe, so it is difficult to identify the phase purity of CZTSSe lms just by XRD characterization. The Raman spectra can be used as an effective tool to differentiate these impurities.…”
Section: Characterizationsmentioning
confidence: 99%
“…

postdeposition alkali treatment to improve heterojunction diode quality in Cu(In,Ga) Se 2 (CIGS) solar cells and chloride treatment to passivate grain boundaries in CdTe solar cells. [3] Although the dominant limiting factors for this low performance are a matter of considerable discussion, [4] the following observations are consistent among kesterite absorbers: i) a low photoluminescence quantum yield (PLQY) and a short chargecarrier lifetime, [5] ii) a high value of Urbach band tail energy (larger than 30 meV for S-rich kesterites) and lack of a steep absorption onset, [6,7] and iii) the presence of secondary phases. [2] However, kesterite-based solar cells, such as Cu 2 ZnSn(S,Se) 4 , which share many of the same characteristics of CIGS and CdTe, significantly lag behind, with a record power conversion efficiency (PCE) of 12.6%.

…”
mentioning
confidence: 99%
“…In order to predict the minimum efficiency of our proposed structure, we have used much less minority carrier life times (0.25-0.52 ns) than that of the reported values in literature (7.1-11 ns). [18,19,23] The detailed simulation procedure and the other electrical and optical parameters along with their references can be found in the Supporting Information.…”
mentioning
confidence: 99%
“…As a result, current density falls significantly with the higher thickness of CZTS (Figure 2(a)) because of the reduced optical power absorption in the bottom cell. Thus, higher thickness of [19] 7 [18] 8.5 [17] 7 [16] Band gap (eV) 1.9 [14] 1.45 [18] 0.97 [17] 0.9 [16] Electron affinity (eV) 3.6 [19] 4.1 [24] 4.05 [17,25] 4.05 [13] Electron effective mass (m e /m o ) 0.37 [14,15] 0.18 [13,16] 0.08 [17] 0.07 [13,16] Hole effective mass (m p /m o ) 1.68 [14] 2 [13,16] 0.3 [17] 0.2 [13,16] Electron mobility (cm 2 V À1 s À1 ) 3 0 [26] 40 [21,24] 75 [23] 145 [13,21] Hole mobility (cm 2 V À1 s À1 ) 1 0 [27] 25 [21] 1 [17,23] 35 [13,21] Acceptor concentration (cm…”
mentioning
confidence: 99%